Ragamala Architecture: Architecture of Melodic Garlands - Tasnim, Zarrin (MAJ - Malaysia Architectural Journal, 2025)
Excluding limited exemptions, the mainstream architecture of Bangladesh is now lost into oblivion. The current architecture is ensuing, the aesthetic of the Western-hemisphere, blind folded, negating the necessity of the Eastern-hemisphere, precisely tropical Dhaka, Bangladesh, portraying high air temperatures and torrential rainfall. The architecture of Bengal, partial India and Bangladesh has affluent architectural history rooted in its culture, religion, and heritage. Traveling back to the centuries in search for insights, the author stumbled upon Ragamala and Bangla Ragamala Paintings, traditional Indian and Bengali paintings, depicting musical modes. Traveling forward to the present, this study quests for a climate receptive core elements that the contemporary architecture could embrace upholding the culture and heritage of Bengal. Conducting literature review and field survey from ancient to modern and contemporary architecture of Indian subcontinent, Bengal and Pavilion models including Ragamala and Bangla Ragamala paintings, this research finds some fundamental features that could work magic in present Dhaka. This research terminates at the framework of designing buildings with extended roof protecting from scorching-sun and torrential-rain, higher plinth, and bare minimum or almost no wall allowing soothing-breeze on a lush-green and water-based landscape could be climate responsive solution for this region. This research culminates quoting Gautama Siddhartha during his nirvana, “Architect, you shall not build your house again,”. This research is not abandoning building architecture like Buddhist Metaphor, rather restating the metaphor, Architect, you shall build, merely break the walls of your house, almost. This research usher an inception of a novel era of architecture towards a sustainable city evolving from the core building models of indigenous essence.